A quietist Jihadi the ideology and influence of Abu Muhammad al-Maqdisi - Wagemakers, Joas 1979- (Cambridge University Press, 2012)
Since 9/ll, the Jordanian Abu Muhammad al-Maqdisi (b. West Bank, 1959) has emerged as one of the most important radical Muslim thinkers alive today. While al-Maqdisi may not be a household name in the West, his influence amongst like-minded Muslims stretches across the world from Jordan, where he lives today, to Southeast Asia. His writings and teachings on Salafi Islam have inspired terrorists from Europe to the Middle East, including Abu Muṣʻab al-Zarqawi, the former leader of al-Qaida in Iraq, and Ayman al-Zawahiri, Osama Bin Laden's successor as the head of al-Qaida Central. This groundbreaking book, which is the first comprehensive assessment of al-Maqdisi, his life, ideology, and influence, is based on his extensive writings and those of other jihadis, as well as on interviews that the author conducted with former jihadis, including al-Maqdisi himself. It is a serious and intense work of scholarship that uses this considerable archive to explain and interpret al-Maqdisi's particular brand of Salafism. More broadly, the book offers an alternative, insider perspective on the rise of radical Islam, with a particular focus on Salafi opposition movements in Saudi Arabia and Jordan.